Реалізація культурної та крос-культурної соціалізіції у вищій школі сучасної України - Шеїна, Лариса Олександрівна (Univerzita Palackého v Olomouci, 2010)
The article is devoted to the possibilities given by higher school in cultural and cross-cultural socialisation. We proclaim that both kinds of socialisation can be realized when students study and spend their free time in a higher educational establishment. One of effective means of socialization is students self-governing
Keywords: культурна соціалізація; крос-культурна соціалізація; світосприйняття; традиції; культурні особливості; культурна спадщина; культурний центр; cultural socialisation; cross-cultural socialisation; higher school; self-governing